METODE PEMBELAJARAN AUDIOLINGUAL DENGAN PODCAST UNTUK MENINGKATKAN KEMAHIRAN MENYIMAK (MAHARAT AL-ISTIMA') PADA MAHASISWA - Novi Anisyah; Faisal Hendra (Berajah Journal, 2023)
Humans as social beings are used to interacting and using language as a means of communication. Especially in the era of globalization, communication between countries is very likely to occur so that interest in mastering foreign languages increases, one of which is Arabic. Arabic is one of the foreign languages for Indonesia, so to master it requires guided learning. The most basic thing to learn a language is to improve listening skills. The ability to listen is very important in learning Arabic which is unique from grammar to sound. Thus, it is necessary to have a method capable of supporting this, one of which is the audiolingual method. This research uses qualitative research - descriptive. The results of this study state that audiolingual learning with podcasts in improving listening skills for Arabic students is very useful, because it will train their hearing and understanding of Arabic audio. Utilization of learning media in the form of podcasts is an effort to increase students' positive responses in receiving material.